Multiple Myeloma Presenting as Acute Liver Failure. Issue 1 (2017) - Cull, Stephanie; Westrich, David J.; Bhatia, Ruchi; Lai, Jinping; Befeler, Alex S.
ABSTRACT : N/A: Liver failure is rarely caused by multiple myeloma (MM). We present an unusual case of MM initially presenting as acute liver injury. A 79‐year‐old man with new‐onset fatigue, decreased appetite, and no history of liver disease was found to have evidence of hepatic decompensation. Liver biopsy demonstrated diffuse plasma cell infiltration, and MM was confirmed with bone marrow biopsy. Chemotherapy was initiated, but the patient decompensated and died due to respiratory failure. MM should be considered on the differential for acute decompensated liver disease. Hepatic involvement of MM at presentation is a poor prognostic indicator, and prompt initiation of treatment can be life‐saving.